2021
DOI: 10.1186/s12964-021-00758-3
|View full text |Cite
|
Sign up to set email alerts
|

PI3K-AKT, JAK2-STAT3 pathways and cell–cell contact regulate maspin subcellular localization

Abstract: Background Maspin (SERPINB5) is a potential tumor suppressor gene with pleiotropic biological activities, including regulation of cell proliferation, death, adhesion, migration and gene expression. Several studies indicate that nuclear localization is essential for maspin tumor suppression activity. We have previously shown that the EGFR activation leads to maspin nuclear localization in MCF-10A cells. The present study investigated which EGFR downstream signaling molecules are involved in masp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Signal transduction can exert a synergistic effect while reinforcing signaling mediated through crosstalk among pathways. Examples include the effect of STAT3 activation on the Ras and PI3K/Akt pathways and the connections of JAK2 with the PI3K and ERK pathways [155][156][157][158][159][160] . Thus, the effects of splice variants may be broader than those identified in a single pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Signal transduction can exert a synergistic effect while reinforcing signaling mediated through crosstalk among pathways. Examples include the effect of STAT3 activation on the Ras and PI3K/Akt pathways and the connections of JAK2 with the PI3K and ERK pathways [155][156][157][158][159][160] . Thus, the effects of splice variants may be broader than those identified in a single pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, maspin-S176 was slightly more exposed (Figure S4A,B), which should favor nuclear localization; however, for antitumor activity, more than one variable may be involved. Furthermore, maspin cellular localization is regulated by cellular confluency and epidermal growth factor receptor-related pathways, implicating their role in maspin function . Nuclear-localized maspin inhibits breast cancer proliferation .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, maspin cellular localization is regulated by cellular confluency and epidermal growth factor receptor-related pathways, implicating their role in maspin function. 62 Nuclear-localized maspin inhibits breast cancer proliferation. 13 Similarly, Dzinic et al reported that nuclear-localized maspin effectively inhibits HDAC1 functions and suppresses the growth of multiple cancer cell lines, including lung and prostate, and that nuclear localization is favored by mutations around the RCL region (maspin-D346E).…”
Section: Discussionmentioning
confidence: 99%
“…4A & B) that should favor nuclear localization, however, for antitumor activity, there may be more than one variable involved. Further, maspin cellular localization is regulated by cellular confluency and epidermal growth factor receptor-related pathways implicating their role in maspin functions (Longhi et al ., 2021). Nuclear localized maspin has been reported to inhibit breast cancer proliferation (Tanaka et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%